Trends in clinically significant anxiety, depression, suicidal ideation and service utilisation among US medical students, 2018–2023 - Xue Du; Yusen Zhai; Laurence M Boitet; John Soldner; Jennifer D Lockman (BMJ Mental Health)
Background Medical students experience disproportionately high rates of anxiety and depression, and treatment gaps may exist. To date, little is known about how these mental health outcomes have changed over time.Objective To examine recent trends in clinically significant anxiety, depression, suicidal ideation, and counselling service utilisation among US medical students.Methods We analysed five waves of the Healthy Minds Study throughout the academic years between 2018 and 2023. The analytic sample comprised 5313 students enrolled in MD programmes from diverse US universities. Study outcomes included clinically significant anxiety, depression, past-year suicidal ideation, and current counselling use. Weighted prevalences were calculated, and sample-weighted multivariable logistic regression, adjusted for age, sex, race/ethnicity, international status, and socioeconomic status, estimated temporal trends.Findings Between 2018 and 2023, the prevalence of anxiety increased by 12.3 percentage points from 21.6% to 33.9%, depression increased by 13.1 percentage points from 14.0% to 27.1%. and counselling service utilisation increased by 17.2 percentage points from 6.7% to 23.9%. These upward trends remained statistically significant even after adjustment for participants’ demographic differences. Suicidal ideation prevalence remained relatively stable over the same period.Conclusions The prevalence of anxiety and depression among US medical students have increased since 2018, paralleled by more but still insufficient counselling utilisation, suggesting a persistent treatment gap. Suicidal ideation remains concerning among this population with higher acquired capability for suicide over their lifespan.Clinical implications Medical schools should transform temporary support initiatives into enduring institutional strategies and foster school climates that enhance protective factors to promote medical students’ well-being.